Characterizing executive functioning and associated behaviors in individuals with dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) syndrome - Rea, Hannah M.; Webb, Sara Jane; Kurtz-Nelson, Evangeline C.; Hudac, Caitlin M.; Bernier, Raphael A.; Miles, Conor; Earl, Rachel; Whiting, Alana; Eayrs, Curtis; Johansson, Margaret; Wang, Tianyun; Eichler, Evan E.; et al. (Frontiers in Neuroscience, 2025)
IntroductionDYRK1A, a protein kinase located on human chromosome 21, plays a role in postembryonic neuronal development and degeneration. Alterations to DYRK1A have been consistently associated with cognitive functioning and neurodevelopmental disorders (e.g., autism, intellectual disability). However, the broader cognitive and behavioral phenotype of DYRK1A syndrome requires further characterization. Specifically, executive functioning, or cognitive processes that are necessary for goal-directed behavior, has not yet been characterized in this population.MethodsIndividuals with DYRK1A variants (n = 29; ages 4 to 21 years) were assessed with a standardized protocol with multiple measures of executive functioning: Delis-Kaplan Executive Function Schedule, and chronologically age-appropriate caregiver-report forms of the Behavior Rating Inventory of Executive Function (BRIEF) and Achenbach System of Empirically Based Assessment (ASEBA). We first examined the feasibility and appropriateness of established executive functioning measures among participants with DYRK1A syndrome to inform selection of executive functioning tools in future research. We then characterized executive functioning among the group, including associations with other phenotypic features.ResultsNeurocognitive assessments of executive functioning were deemed infeasible due to cognitive and verbal functioning. Caregiver-report revealed elevated executive functioning concerns related to self-monitoring, working memory, and planning/organization on the BRIEF, and attention and ADHD on the CBCL. Only two participants had existing ADHD diagnoses; however, 5 participants (out of 10 participants with data) exceeded the cutoff on the BRIEF, 13 individuals (out of 27 with data) exceeded the cutoff on the ASEBA ADHD subscale, and 18 exceeded the cutoff on the ASEBA attention subscale. There was concordance between ADHD diagnosis and the ASEBA, but not BRIEF. Executive functioning was correlated with nonverbal IQ and autism traits.DiscussionObjective measures of executive functioning are needed for individuals with intellectual disability who are nonverbal and/or have motor limitations. Diagnostic overshadowing, or the tendency to attribute all problems to intellectual disability and to leave other co-existing conditions, such as executive functioning challenges or ADHD, undiagnosed, is common. Phenotypic characterization of executive functioning is therefore important for our understanding of DYRK1A syndrome and for ensuring that caregivers’ concerns are addressed, and individuals receive the clinical services that best meet their needs.